Weekly Intraperitoneal Injection of Tamoxifen in an Inducible In Vivo Model of Junctional Epidermolysis Bullosa Generates Early and Advanced Disease Phenotypes - Eleri Mai Jones; Priya Garcha; Monique Aumailley; Edel Anne O’Toole; Emanuel Rognoni; Matthew Caley (JID Innovations)
Junctional epidermolysis bullosa caused by loss-of-function variants in genes encoding the skin basement membrane proteins laminin 332, type XVII collagen, or integrin α6β4 affects patients from birth with severe blistering, eventually leading to scarring and early lethality. In this study, we have optimized a previously published junctional epidermolysis bullosa–knockout mouse model with weekly tamoxifen intraperitoneal injections, resulting in a more controllable and severe model. Owing to the titratable dosing, this model now recapitulates both early and advanced stages of the human disease, strengthening its use in therapeutic studies. The gradual loss of laminin-α3 in the skin of the mouse through weekly injections lead to generalized blistering and fibrotic dermal changes in multiple skin sites by week 12 after tamoxifen. Our findings demonstrate the usefulness of optimizing tamoxifen induction in Cre-loxP mouse models of extracellular matrix proteins, an approach that could be applicable to other emerging inducible transgenic disease models to improve their ability to mimic the human disease phenotype.